2021
DOI: 10.3390/pr9010164
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Theory and Modelling of Nanomechanical Sensors for Biological Applications

Abstract: Over the last decades, nanomechanical sensors have received significant attention from the scientific community, as they find plenty of applications in many different research fields, ranging from fundamental physics to clinical diagnosis. Regarding biological applications, nanomechanical sensors have been used for characterizing biological entities, for detecting their presence, and for characterizing the forces and motion associated with fundamental biological processes, among many others. Thanks to the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 105 publications
(145 reference statements)
0
23
0
Order By: Relevance
“…Then, many research groups have demonstrated that nanomechanical sensors can detect not only a variety of targets, such as moisture [ 41 , 42 , 43 ] and mercury vapor [ 41 , 44 ], but also various chemical/physical phenomena, including the formation of a self-assembled monolayer [ 45 ], DNA hybridization [ 46 , 47 , 48 ], a single spin [ 49 , 50 ], and quantum state [ 51 , 52 ]. Regarding the working principle of nanomechanical sensors whose flexible structures deform at the nanoscale, they are following two major types of operation modes: the static mode and dynamic mode [ 32 , 53 , 54 , 55 , 56 , 57 , 58 ]. In this section, we will briefly review these two operation modes.…”
Section: Nanomechanical Sensorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Then, many research groups have demonstrated that nanomechanical sensors can detect not only a variety of targets, such as moisture [ 41 , 42 , 43 ] and mercury vapor [ 41 , 44 ], but also various chemical/physical phenomena, including the formation of a self-assembled monolayer [ 45 ], DNA hybridization [ 46 , 47 , 48 ], a single spin [ 49 , 50 ], and quantum state [ 51 , 52 ]. Regarding the working principle of nanomechanical sensors whose flexible structures deform at the nanoscale, they are following two major types of operation modes: the static mode and dynamic mode [ 32 , 53 , 54 , 55 , 56 , 57 , 58 ]. In this section, we will briefly review these two operation modes.…”
Section: Nanomechanical Sensorsmentioning
confidence: 99%
“…The cantilever-type sensors can detect two physical parameters: volume and/or mass of target molecules. To measure the volume and mass of target molecules, there are two different operation modes as mentioned above: dynamic and static modes ( Figure 3 ) [ 32 , 53 , 54 , 55 , 56 , 57 , 58 ]. While the static mode detects changes in the deformation state of a nanomechanical sensor, the dynamic mode detects changes in the mechanical resonances.…”
Section: Nanomechanical Sensorsmentioning
confidence: 99%
See 3 more Smart Citations